2007
DOI: 10.1111/j.1095-8649.2007.01674.x
|View full text |Cite
|
Sign up to set email alerts
|

Is genetic variability so important? Non‐native salmonids in South America

Abstract: Three salmonid species introduced in Patagonian national parks in Argentine have experienced different degrees of expansion. Atlantic salmon Salmo salar is restricted to a few river‐lake systems and its populations have been declining over recent years. Both rainbow Oncorhynchus mykiss and brown trout Salmo trutta populations have expanded from their introduction sites and now occupy a wide range of freshwater ecosystems. Genetic variation at the same neutral markers (microsatellite loci) was examined for diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Based on reduced genetic variability of Patagonian brown trout, Valiente et al (2007) suggested founder effects and bottlenecks that were not an obstacle for its expansion. The objectives of the present study were two-fold.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Based on reduced genetic variability of Patagonian brown trout, Valiente et al (2007) suggested founder effects and bottlenecks that were not an obstacle for its expansion. The objectives of the present study were two-fold.…”
Section: Introductionmentioning
confidence: 98%
“…Although the region has experienced intense damming during the last 30 years (Mugetti et al 2004), which is a priori a potential risk for long-term survival of salmonids (Mesquita et al 2005;Whiteley et al 2006;Layman et al 2007), they have successfully adapted to South American ecosystems (Valiente et al 2007). This species exhibits a consistent ability of adapting to adverse environmental conditions, including damming (Ayllon et al 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Salmonids are typical examples of deliberate humanmediated stock movements. For the purposes of fishing and aquaculture, they have been transferred to exotic regions such as South America and New Zealand, where they have adapted and in some cases become invaders (Pascual et al, 2002;Townsend, 2003;Valiente et al, 2007). Large-scale human-mediated stock movements have also occurred between regions within the natural geographic range of a species; for example, in the second half of the XX century farmed salmon and trout from central and north European countries have been transplanted to south European rivers, where native populations already existed (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…1995, Jensen et al 2000, Valiente et al 2007). However, a review of the applicability of Bergmann's rule (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Broadly speaking, several factors strongly influence salmonid growth, including temperature, trophic status, population density, and latitude (Elliott et al 1995, Jensen et al 2000, Valiente et al 2007). However, a review of the applicability of Bergmann's rule (i.e.…”
Section: Discussionmentioning
confidence: 99%